1964
DOI: 10.1126/science.145.3634.819
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Metabolism in L Cells Infected with a Member of the Psittacosis Group

Abstract: thranilic oxidase in these livers, it may be concluded that the failure of diabetic animals to synthesize nicotinic acid is not caused by a decrease in any essential enzyme, but must be attributed to some other type of control mechanism. The striking increase in picolinic carboxylase, from immeasurably low concentration to appreciable concentration, has previously been correlated with the decreased production of nicotinic acid. The decrease in quinolinic acid formation caused by an increase in picolinic carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1966
1966
1988
1988

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The titer of both intracellular and extracellular infections began to rise 10 hr after infection, and reached its peak at 40 hr. Growth of the meningopneumonitis agent in the cloned L cells differed from that in the uncloned L cells used previously (28) in that multiplication continued for about 10 hr longer, reached a terminal titer more than 1 log higher, and resulted in a slower rate of killing of the host cells.…”
Section: Growth Ofthe Meningopneumonitis Agent In Clonementioning
confidence: 66%
See 2 more Smart Citations
“…The titer of both intracellular and extracellular infections began to rise 10 hr after infection, and reached its peak at 40 hr. Growth of the meningopneumonitis agent in the cloned L cells differed from that in the uncloned L cells used previously (28) in that multiplication continued for about 10 hr longer, reached a terminal titer more than 1 log higher, and resulted in a slower rate of killing of the host cells.…”
Section: Growth Ofthe Meningopneumonitis Agent In Clonementioning
confidence: 66%
“…Table 6 compares the effect of meningopneumonitis infection on incorporation of labeled precursors into the RNA and DNA of the nuclei of uncloned and cloned L cells. The data on uncloned cells were obtained with a P32-orthophosphate label (28), but more recent use of a H3-cytidine label has yielded identical results. The effect of infection on nucleic acid synthesis in the two closely related L cell lines differed greatly.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Members of the genus Chlamydia inhibit macromolecular synthesis in their host cells, particularly the synthesis of deoxyribonucleic acid (DNA); DNA synthesis is inhibited first and to a greater extent than synthesis of ribonucleic acid (RNA) and protein (42,43). The host genome is not degraded during the early stages of infection (25), so that loss of the template is not responsible for the inhibition.…”
mentioning
confidence: 99%
“…The host genome is not degraded during the early stages of infection (25), so that loss of the template is not responsible for the inhibition. Crocker and his associates (6) suggested that the inhibition of host DNA synthesis results from competition between the host cell and the parasite for cytoplasmic resources, whereas Schechter et al (43) and Schechter (42) postulated a specific inhibitory action on the part of the parasite.…”
mentioning
confidence: 99%